TINJAUAN TEORI PERENCANAAN DALAM PELAKSANAAN PROGRAM PEMANFAATAN DANA DESA - Yeni Nur Afifah (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
The Law Number 6 of 2014 concerning Villages has made the villages as spearhead of efforts to equalize development and improve the people welfare in Indonesia. Since the beginning of the disbursement, the Village Fund has continued to be spotlight, as the amount is quite large and always increases every year. Considering the programs carried out through the use of Village Funds are actually development programs, it should have been included in planning studies so that the objectives achieved can be realized optimally. The approach taken in this study is a deductive approach, started from theory and literature review and then become a reference in studying the object of research. The analysis method used descriptive qualitative method with data obtained from in-depth interviews and document studies with purposive sampling sampling technique which is continued to snow-ball sampling. From 2015 to 2018, Jatiroto Village has produced six development products from the Village Fund utilization program, namely village roads, road grafts, agricultural roads, revitalization of volleyball courts, construction of village shops, and equity participation in BUMDes. Based on the results and previous discussion, it turns out that the programs being run are not in accordance with general planning theory.